Mothers' adjustments returning to onsite work in Quezon City after COVID-19 pandemic - Sagun, Lauryn Izabelle U.; Sundiang, Sofia Louise B.; Tongson, Excelsa C. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
This qualitative study aimed at understanding the adjustments made by employed mothers of toddlers in their return to onsite work after the COVID-19 pandemic. To provide an in-depth discussion of the experiences of these mothers, this study describes the adjustments they made in returning to onsite work, the factors that influence the adjustments they made, and the workplace policies and programs that hinder or support them in their return to onsite work. Twenty mothers employed in Quezon City who gave birth during the pandemic participated through purposive and snowball sampling methods. To ensure that the experiences of employed mothers from private and government institutions are well-accounted for, seven participants are employed in private institutions and thirteen participants are employed in a state university. These mothers come from different fields of work; although, generally dominated by educators and administrative officers and staff. Thematic analysis was used to analyze the data collected. Findings show that employed mothers went through a lot of adjustments in their transition to onsite work, including changes in childcare setup, changes in unpaid work routine, and even change in mindset. Although the participants shared a multitude of challenges, the presence of workplace policies and programs that support employed mothers significantly helped them in balancing their roles as a parenting mother and an employed worker.
Thesis
Includes bibliographical references (pages 160-170)
Keywords: Working mothers -- Philippines; Child care -- Philippines; COVID-19 pandemic -- Philippines